AB0063 Resveratrol Suppresses Crystal-Induced Inflammation in Vitro by Inhibiting Cytokine Production. (9th June 2015) - Oliviero, F.; Scanu, A.; Galozzi, P.; Sfriso, P.; Frallonardo, P.; Ramonda, R.; Spinella, P.; Punzi, L.
Abstract : Background: Crystal-induced inflammation is characterized by a marked release of cytochines, chemokines and other factors in the synovial compartments. The resolution of this process is quite easy to achieve in patients through the use of NSAIDs and other more specific drugs such as colchicines and anti-IL1β biologics. In view of the potential long term adverse effects of these drugs, we aimed to investigate the role of a small polyphenolic compound, resveratrol (RES), best known as a constituent of grapes and wine. Objectives: We used a monocytic cell line to assess the effect of RES in monosodium urate (MSU) and calcium pyrophosphate (CPP) crystal-induced inflammation. Methods: THP-1 cells were stimulated with synthetic MSU (0.05mg/ml) and CPP (0.025mg/ml) crystals after a 3h priming with phorbol myristate acetate (PMA) (100ng/ml). Resveratrol was added to cultures at 10μM. Epigallocatechin-3-gallate (EGCG), an already known nutraceutic inhibitor of crystal-induced inflammation (1), was used as control at the same concentration. The cytokines IL-1β, IL-8 and TGFβ were determined in the culture supernatants by ELISA assays. To assess whether RES could interfere with crystal internalization, the phagocytosis index was calculated at different time points. These experiments were preceded by the evaluation of the role of phagocytosis on cytokine release by using cytochalasin D at 1μM. Results: After the 3h of priming with PMA, THP-1 cells produced high basal levels of both IL-1β and IL-8 and these further increased after 24h treatment with MSU and CPP crystals. The addition of RES together with the stimulus lead to a marked decrease in IL-1β (3 fold and 5 fold in presence of CPP and MSU respectively) and IL-8 release (2 fold and 3 fold in presence of CPP and MSU respectively). The inhibition of the inflammatory response by RES was dose-dependent. As regards TGFβ, EGCG showed a greater inhibition with respect to RES which, in any case, showed a 1.7 and 1.5 fold inhibition when added to cultures simultaneously to CPP and MSU respectively. The kinetic study showed a rapid internalization of crystals. Within 24 hours 50% of crystals were actively phagocytized by the cells and RES did not show any inhibitory effect on crystal phagocytosis. Conclusions: The results of this study highlighted the anti-inflammatory potential of resveratrol in crystal-induced inflammation. Although the possible mechanism by which resveratrol exerts its biological functions is under evaluation (using sirtuin inhibitors), the direct effect on the inflammatory outcome may have important implications in the prevention and treatment of crystal-related arthropathies. References: Oliviero F, Sfriso P, Scanu A, Fiocco U, Spinella P, Punzi L. Epigallocatechin-3-gallate reduces inflammation induced by calcium pyrophosphate crystals in vitro. Front Pharmacol 2013;4:51 Disclosure of Interest: None declared